LEGAL PROTECTION FOR TEACHERS AS VICTIMS OF VIOLENCE IN THE IMPLEMENTATION OF PROFESSIONAL DUTIES IN SCHOOLS - Budoyo, Sapto; Khansa Pramesti, Fahrinda (Jurnal Meta-Yuridis, 2026)
Teachers are one of the key elements in the implementation of national education who have an important role in shaping the character, morals, and intelligence of students. in accordance with the provisions of Law Number 14 of 2005 concerning Teachers and Lecturers, which emphasizes that teachers have the right to receive protection when carrying out their professional duties, including legal protection, professional protection, and protection of occupational safety and health. This study uses a normative legal research method, by implementing a legislative approach and a conceptual approach. There is a fairly clear legal basis for protecting teachers as victims of violence in carrying out professional duties in schools. Law Number 14 of 2005 concerning Teachers and Lecturers guarantees legal protection, professional protection, and occupational safety and health for teachers when carrying out their duties. In addition, Law Number 20 of 2003 concerning the National Education System emphasizes the importance of organizing education in a safe and conducive atmosphere.